Electroluminescent cooling using double diode structures - Sadi, Toufik; Radevici, Ivan; Kivisaari, Pyry; Casado, Alberto; Oksanen, Jani (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
The progress in optical cooling in recent years is resulting in a renewed interest in electroluminescent (EL) cooling using conventional III-V semiconductor light emitting diodes (LEDs). In this work, we address the limiting factors for observing EL cooling in III-As intracavity double diode structures (DDSs), at high powers at and close to 300K, by using a combination of experimental characterization and physical device models. The studied DDSs incorporate optically-coupled III-As LED and p-n homojunction photodiode (PD) structures, integrated in a single device and providing a favourable environment for EL cooling observation. We employ a modelling framework coupling the drift-diffusion charge transport model to a photon transport model calibrated using measurements on real devices at different temperatures. Results suggest that the bulk properties of the III-V materials are already sufficient for EL cooling.